Stem rust on barberry species in Europe: Host specificities and genetic diversity - Rodriguez-Algaba, Julian; Hovmøller, Mogens S.; Schulz, Philipp; Hansen, Jens G.; Lezáun, Juan Antonio; Joaquim, Jessica; Randazzo, Biagio; Czembor, Paweł; Zemeca, Liga; Slikova, Svetlana; Hanzalová, Alena; Holdgate, Sarah; et al. (Frontiers in Genetics, 2022)
The increased emergence of cereal stem rust in southern and western Europe, caused by the pathogen Puccinia graminis, and the prevalence of alternate (sexual) host, Berberis species, have regained attention as the sexual host may serve as source of novel pathogen variability that may pose a threat to cereal supply. The main objective of the present study was to investigate the functional role of Berberis species in the current epidemiological situation of cereal stem rust in Europe. Surveys in 11 European countries were carried out from 2018 to 2020, where aecial infections from five barberry species were collected. Phylogenetic analysis of 121 single aecial clusters of diverse origin using the elongation factor 1-α gene indicated the presence of different special forms (aka formae speciales) of P. graminis adapted to different cereal and grass species. Inoculation studies using aecial clusters from Spain, UK and Switzerland resulted in 533 stem rust isolates sampled from wheat, barley, rye and oat, which confirmed the presence of multiple special forms of P. graminis. Microsatellite marker analysis of a subset of 192 sexually-derived isolates recovered on wheat, barley and rye from the three populations confirmed the generation of novel genetic diversity revealed by the detection of 135 multilocus genotypes. Discriminant analysis of principal components resulted in four genetic clusters, which grouped at both local and country level. Here, we demonstrated that a variety of Berberis species may serve as functional alternate hosts for cereal stem rust fungi and highlights the increased risks that the sexual cycle may pose to cereal production in Europe, which calls for new initiatives within rust surveillance, epidemiological research and resistance breeding.